Interferons in Ophthalmology Current Status and Advancing Trends - Shiva Prasad Gantyala; Himanshu Shekhar; M. Vanathi; Rajesh Sinha; Jeewan Singh Titiyal (Delhi Journal of Ophthalmology)
Interferon, a natural multifunctional protein, has been an important part of medical therapy in various ophthalmic indications. Interferons are classified as alpha, beta and gamma interferons based on molecular structure and grouped into types 1 and 2 depending on their cellular effects. Its various actions include antiviral, antiproliferative, immunomodulatory and antiangiogenic effects. Its verstile actions makes it valid indication in treating various intraocular and extraocular diseases. Its local use is indicated in ocular surface neoplasia, viral keratitis, mooren’s ulcer, VKC and systemic use in Behcet’s disease, cystoid macualr edema, AMD and optic neuritis with multiple sclerosis.